On the equivalence groups for (2+1) dimensional nonlinear diffusion equation. (October 2018) - Özer, Saadet
Abstract: (2+1) dimensional diffusion equation is considered within the framework of the group of equivalence transformations. Generators for the group are obtained and admissible transformations between linear and nonlinear equations are examined. It is shown that transformations between linear and nonlinear equations are possible provided that the generators of independent variables depend on the dependent variable. Exact solutions for some nonlinear equations are obtained.